Oleanolic Acid Acetate Alleviates Symptoms of Experimental Autoimmune Encephalomyelitis in Mice by Regulating Toll-Like Receptor 2 Signaling - Kim, Minju; Lee, Soyoung; Lim, Hyungjin; Lee, Jihye; Park, Ji-Young; Kwon, Hyung-Jun; Lee, In-Chul; Ryu, Young-Bae; Kim, Jeongtae; Shin, Taekyun; Ahn, Ginnae; Rho, Mun-Chual; et al. (Frontiers in Pharmacology, 2020)
Toll-like receptor 2 (TLR2) is expressed by several immune cells in the central nervous system and plays an important role in neuroinflammation. Moreover, TLR2 up-regulation has been reported in multiple sclerosis (MS) patients and in experimental autoimmune encephalomyelitis (EAE), a mouse model for multiple sclerosis. Therefore, finding a drug that modulates TLR2 signaling is important for MS treatment. Oleanolic acid acetate (OAA) has anti-inflammatory and immunomodulatory effects. Hence, this study aimed to examine the effects of OAA on TLR2 signaling and neuroinflammation in EAE. EAE was induced in C57/BL6 mice using synthesized myelin oligodendrocyte glycoprotein (MOG) 35-55 peptide, and OAA was administered every day. Hind limb paralysis and inflammatory cell infiltration were observed in the spinal cords of EAE model mice. Moreover, T-cell proliferation was significantly stimulated in splenic cells from EAE model mice. The expression of pro-inflammatory cytokines in the spinal cord was up-regulated, and their serum protein levels were also increased in EAE model mice. Furthermore, up-regulation of TLR2 and downstream signaling molecules was observed in the spinal cord. All these pathological changes were reversed by OAA treatment. Thus, based on our results in EAE, OAA might be a promising therapeutic agent and the TLR signaling pathway a useful therapeutic target for multiple sclerosis.